2004
DOI: 10.1017/s1743921304000225
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the Shapley supercluster

Abstract: Abstract. We present results of our wide-field redshift survey of galaxies in a 285 square degree region of the Shapley Supercluster (SSC), based on a set of 10529 velocity measurements (including 1201 new ones) on 8632 galaxies obtained from various telescopes and from the literature. Our data reveal that the main plane of the SSC (v ≈ 14500 km s −1 ) extends further than previous estimates, filling the whole extent of our survey region of 12 degrees by 30 degrees on the skyThere is also a connecting structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Table 1 gives details of the Kepler AGN whose light curves are presented in this paper, a sample of four variable AGN that Kepler has been observing since Q6. Of these four, only Zw 229−15 (z = 0.0275, Falco et al 1999, Proust 1990) had been identified as an AGN prior to the launch of Kepler. A recent reverberation mapping campaign found it had an Hβ lag Note.…”
Section: Source Selectionmentioning
confidence: 99%
“…Table 1 gives details of the Kepler AGN whose light curves are presented in this paper, a sample of four variable AGN that Kepler has been observing since Q6. Of these four, only Zw 229−15 (z = 0.0275, Falco et al 1999, Proust 1990) had been identified as an AGN prior to the launch of Kepler. A recent reverberation mapping campaign found it had an Hβ lag Note.…”
Section: Source Selectionmentioning
confidence: 99%
“…Despite being relatively bright, its position in the galactic plane has E-mail : adegoke@physics.iisc.ernet.in † E-mail : suvendu.rakshit@iiap.res.in ‡ E-mail : bm@physics.iisc.ernet.in resulted in there being very little known about this source (Carini & Ryle, 2012). Its Seyfert nature was noted by Proust (1990) and it was observed in the ROSAT all sky survey by Zimmermann et al (2001). Barth et al (2011) carried out a ground based reverberation mapping campaign on the source to complement its scheduled observation with the Kepler mission.…”
Section: Introductionmentioning
confidence: 99%